Omani Post Basic Education Students' Attitudes towards National Identity - Ahmad Al Rabaani (Sultan Qaboos University, 2017)
The study aimed at investigating Omani post basic education students' attitudes towards national identity. Data was collected by using a questionnaire consisting of -36- items which fall under five domains. The questionnaire was checked for both validity and reliability. The study sample consisted of -1928- male and female students from five provinces in Oman. The results showed that Omani post basic education students were highly proud of their national identity and showed concern for the embodiment and representation of their national identity in their behavior. They also showed a high level of rejection of all types of behavior that are contrary to national identity. Moreover, they showed great fear of the threat to national identity. In addition, they strongly supported the enhancement of national identity through national and social events. The results also revealed that there were significant differences between males and females where females showed a higher level of pride in their national identity than their male counterparts, whereas males showed a high level of fear of the threat sources to national identity. The study recommended continuously promoting national identity through national and social events.